A systematic review of non-specific and specific treatment factors associated with lower or greater internalising and externalising symptoms in therapeutic residential care. (April 2023) - Castro, Emma; Magalhães, Eunice; del Valle, Jorge Fernández
Highlights: Six non-specific treatment factors and five specific treatment factors identified. One specific and four non-specific treatment factors appear in multiple studies. More research is required to replicate findings. TRC should include general components and specified approaches to sub-groups. Abstract: Background: There is limited evidence on how Therapeutic Residential Care (TRC) achieves treatment goals: TRC remains too much of a "black box". We need to know more about how results are achieved, rather than merely investigating the achieved results. Objective: This systematic review aimed to synthesize quantitative literature regarding the associations between non-specific and specific treatment factors and lower or greater internalising and externalising symptoms. Method: Following PRISMA guidelines, a systematic literature search was conducted in July 2021. Of the 2, 409 records screened, 40 articles, composed of 38 samples were included. Results: A total of six non-specific treatment factors (individual, family, academic history, symptoms, abuse and trauma history and relationships) and five specific treatment factors (treatment model, therapeutic intervention, placement decision making, environment and staffing) were reported. Conclusion: Only four non–specific treatment factors and one specific treatment factor appeared in multiple studies while all other factors and sub-factors were not replicated. More research is required to replicate and explore possible specific and non-specific treatment factors associated with internalising and externalising symptoms. The reviewed literature suggested that TRC should target a myriad of non-specific and specific treatment factors to increase the likelihood of success and that family involvement may be a particularly crucial component. Future research should focus on longitudinal studies that explore the long-term impact of non-specific and specific treatment factors on youth during placement and beyond.